Prone mechanical ventilation in acute brain injury - Suresh, Varun; Sharma, Saurabh (Critical care (London, England), 2021)
[...]we infer that to ensure uniformity of ICP data studied the authors must have used intra-parenchymal catheter-based technique of ICP measurement. [...]we presume this heterogeneity contributed to the insignificant results of PP on ICP among patients whom underwent major ICP lowering interventions like craniectomy (p = 0.595), barbiturate coma (p = 0.694) and osmotherapy (p = 0.440). Rights and permissions Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made.